Pengembangan Kualitas Industri Rumah Tangga melalui Sertifikasi Halal Produk Pangan Olahan di Kota Singkawang, Kalimantan Barat - Afra Roki; Sri Widiyastuti; Rachmawati; Yaniza, Tiza (Lembaga Dongan Dosen, 2024)
Household industries play a significant role in supporting the local economy, particularly in Singkawang City, West Kalimantan, which is renowned for its specialty food products. However, limited legal awareness and restricted access to halal certification are major challenges faced by micro, small, and medium enterprises (MSMEs). This community engagement program aims to enhance MSMEs' quality through halal certification training and education on consumer protection law. The methods employed include lectures, interactive discussions, and technical assistance to help business owners understand halal certification procedures in compliance with regulations. The results show a significant increase in business owners' understanding of the importance of formal halal certification and standardized food packaging. The conclusion emphasizes the need for continued similar programs with broader coverage to support MSME development, enhance product competitiveness, and ensure better consumer protection.